The interpretation of the flesh: Freud and femininity - Brennan, Teresa (Routledge, 1992)
The 'riddle of femininity', like Freud's reference to women's sexuality as a 'dark continent', has been treated as a romantic aside or a sexist evasion rather than as a problem to be solved. In this first comprehensive study, Teresa Brennan suggests that by placing these ideas in the context of Freud's work as a whole, we will begin to understand why femininity was such a riddle for Freud. Brennan argues that by turning to Freud's work and his concrete questions about femininity, a psychical state which occurs in men and women alike, the problem is clearly a soluble one, provided that Freud's concern with energy is taken into account. The real riddle of femininity is as much a problem for thinking about physicality as a problem for the subject who suffers from what Freud described as 'femininity's negative effects on curiosity, intelligence and activity.
Keywords: 1900-1999; cours; discipline; fem1000; féminité; histoire; premier cycle; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; violences

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis